Multidimensional, quantitative assessment of PD-1/PD-L1 expression in patients with Merkel cell carcinoma and association with response to pembrolizumab. Issue 1 (1st October 2018) - Giraldo, Nicolas A.; Nguyen, Peter; Engle, Elizabeth L.; Kaunitz, Genevieve J.; Cottrell, Tricia R.; Berry, Sneha; Green, Benjamin; Soni, Abha; Cuda, Jonathan D.; Stein, Julie E.; Sunshine, Joel C.; Succaria, Farah; et al.
Abstract : Background: We recently reported a 56% objective response rate in patients with advanced Merkel cell carcinoma (MCC) receiving pembrolizumab. However, a biomarker predicting clinical response was not identified. Methods: Pretreatment FFPE tumor specimens ( n  = 26) were stained for CD8, PD-L1, and PD-1 by immunohistochemistry/immunofluorescence (IHC/IF), and the density and distribution of positive cells was quantified to determine the associations with anti-PD-1 response. Multiplex IF was used to test a separate cohort of MCC archival specimens ( n  = 16), to identify cell types expressing PD-1. Results: Tumors from patients who responded to anti-PD-1 showed higher densities of PD-1+ and PD-L1+ cells when compared to non-responders (median cells/mm 2, 70.7 vs. 6.7, p  = 0.03; and 855.4 vs. 245.0, p  = 0.02, respectively). There was no significant association of CD8+ cell density with clinical response. Quantification of PD-1+ cells located within 20 μm of a PD-L1+ cell showed that PD-1/PD-L1 proximity was associated with clinical response ( p  = 0.03), but CD8/PD-L1 proximity was not. CD4+ and CD8+ cells in the TME expressed similar amounts of PD-1. Conclusions: While the binomial presence or absence of PD-L1 expression in the TME was not sufficient to predict response to anti-PD-1 in patients with MCC, we show that quantitative assessments of PD-1+ and PD-L1+ cell densities as well as the geographic interactions between these two cell populations correlate with clinical response. Cell types expressing PD-1 in the TME include CD8+ T-cells, CD4+ T-cells, Tregs, and CD20+ B-cells, supporting the notion that multiple cell types may potentiate tumor regression following PD-1 blockade.